Recurrent de novo missense variants across multiple histone H4 genes underlie a neurodevelopmental syndrome - Tessadori, Federico; Duran, Karen; Knapp, Karen; Fellner, Matthias; Smithson, Sarah; Beleza Meireles, Ana; Elting, Mariet W.; Waisfisz, Quinten; O’Donnell-Luria, Anne; Nowak, Catherine; Douglas, Jessica; Ronan, Anne; et al. (The American journal of human genetics, 2022)
Chromatin is essentially an array of nucleosomes, each of which consists of the DNA double-stranded fiber wrapped around a histone octamer. This organization supports cellular processes such as DNA replication, DNA transcription, and DNA repair in all eukaryotes. Human histone H4 is encoded by fourteen canonical histone H4 genes, all differing at the nucleotide level but encoding an invariant protein. Here, we present a cohort of 29 subjects with de novo missense variants in six H4 genes (H4C3, H4C4, H4C5, H4C6, H4C9, and H4C11) identified by whole-exome sequencing and matchmaking. All individuals present with neurodevelopmental features of intellectual disability and motor and/or gross developmental delay, while non-neurological features are more variable. Ten amino acids are affected, six recurrently, and are all located within the H4 core or C-terminal tail. These variants cluster to specific regions of the core H4 globular domain, where protein-protein interactions occur with either other histone subunits or histone chaperones. Functional consequences of the identified variants were evaluated in zebrafish embryos, which displayed abnormal general development, defective head organs, and reduced body axis length, providing compelling evidence for the causality of the reported disorder(s). While multiple developmental syndromes have been linked to chromatin-associated factors, missense-bearing histone variants (e.g., H3 oncohistones) are only recently emerging as a major cause of pathogenicity. Our findings establish a broader involvement of H4 variants in developmental syndromes.